A Decomposition and Noise Removal Method Combining Diffusion Equation and Wave Atoms for Textured Images. (16th May 2010) - Casaca, Wallace Correa de Oliveira; Boaventura, Maurílio
Abstract : We propose a new method that is aimed at denoising images having textures. The method combines a balanced nonlinear partial differential equation driven by optimal parameters, mathematical morphology operators, weighting techniques, and some recent works in harmonic analysis. Furthermore, the new scheme decomposes the observed image into three components that are well defined as structure/cartoon, texture, and noise-background. Experimental results are provided to show the improved performance of our method for the texture-preserving denoising problem.